Did trade unions protect employees’ mental health during the COVID-19 pandemic? A mixed effects model using UK data from Understanding Society - Alastair H Leyland; Srinivasa Vittal Katikireddi; Evangelia Demou; Theocharis Kromydas; Jacques Wels (BMJ Public Health, 2025)
Introduction Few studies have addressed the relationship between trade unions and workers’ mental health during the COVID-19 pandemic.Methods We analysed panel data from Understanding Society collected before and during the COVID-19 pandemic (49 915 observations; 5988 respondents) to assess the relationship between union presence within the workplace and union membership and a binary measure of common mental disorders (CMD), the 12-Item General Health Questionnaire (>4, probable psychological distress). A mixed-effect log-linear model assessed effect heterogeneity across time and industries, with average marginal effects (AME) indicating effect differences between groups.Results Of our sample, 49.1% worked in a unionised workplace, with 53.8% of them being union members. Approximately 25% of the entire workforce was trade union members. Psychological distress prevalence was higher during the pandemic (25.4%) compared with prepandemic (18.4%). Union presence ((AMEpre-pandemic: 1.0, 95% CI−0.66 to 2.70) (AME-pandemic: −0.2, 95% CI−1.91 to 1.58)) and union membership ((AMEpre-pandemic: 1.6, 95% CI −0.69 to 3.93) (AMEpandemic: −0.1, 95% CI −2.29 to 2.00)) were both associated with modest protection against CMD risk. Although, industry heterogeneity exists.Conclusions Trade union presence may have a protective effect on workers’ mental health in periods of crisis, such as during a pandemic. Within unionised workplaces, trade union membership further mitigated the negative effects of the pandemic on mental health. Collective negotiation may be protective in periods of uncertainty, benefiting all workers.